Exploring Learning Needs for ‘Pesona Gege’: A Study on Civic Education in Primary Schools - Sari, Indah Kurnia; Ibda, Hamidulloh; Harun, Makmur (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
This study analyzes the needs of primary school teachers and students concerning the development of a culture-based educational game titled Pesona Gege for the Pendidikan Pancasila dan Kewarganegaraan (PPKn) subject. Employing a quantitative cross-sectional survey method, the research engaged respondents from five Madrasah Ibtidaiyah in Kandangan District, comprising five teachers and twenty students. Data were collected through structured questionnaires and analyzed descriptively. The findings reveal that 100% of teachers and 85–100% of students demonstrated a high demand for educational media that is interactive, culturally relevant, and accessible across multiple platforms. Teachers highlighted the importance of capacity-building initiatives in Genially-based game development, whereas students emphasized preferences for rich visual content and the use of the Indonesian language. These results underscore an urgent need for the development of culturally grounded, student-centered educational media to strengthen national character education. This study contributes to the field by providing empirical evidence on the integration of local cultural elements into digital educational tools, positioning digital games as a strategic medium for actualizing the Profil Pelajar Pancasila through engaging and contextually meaningful learning experiences. Furthermore, the research offers practical insights for curriculum designers and educational technology developers aiming to enhance civic education in primary schools through culturally responsive digital innovation.